Interfacial Engineering of Bifunctional Niobium (V)‐Based Heterostructure Nanosheet Toward High Efficiency Lean‐Electrolyte Lithium–Sulfur Full Batteries. (28th April 2021) - Shi, Haodong; Qin, Jieqiong; Lu, Pengfei; Dong, Cong; He, Jian; Chou, Xiujian; Das, Pratteek; Wang, Jiemin; Zhang, Liangzhu; Wu, Zhong‐Shuai
Abstract: High‐efficiency lithium–sulfur (Li–S) batteries depend on an advanced electrode structure that can attain high sulfur utilization at lean‐electrolyte conditions and minimum amount of lithium. Herein, a twinborn holey Nb4 N5 –Nb2 O5 heterostructure is designed as a dual‐functional host for both redox–kinetics–accelerated sulfur cathode and dendrite‐inhibited lithium anode simultaneously for long‐cycling and lean‐electrolyte Li–S full batteries. Benefiting from the accelerative polysulfides anchoring–diffusion–converting efficiency of Nb4 N5 –Nb2 O5, polysulfide‐shutting is significantly alleviated. Meanwhile, the lithiophilic nature of holey Nb4 N5 –Nb2 O5 is applied as an ion‐redistributor for homogeneous Li‐ion deposition. Taking advantage of these merits, the Li–S full batteries present excellent electrochemical properties, including a minimum capacity decay rate of 0.025% per cycle, and a high areal capacity of 5.0 mAh cm −2 at sulfur loading of 6.9 mg cm −2, corresponding to negative to positive capacity ratio of 2.4:1 and electrolyte to sulfur ratio of 5.1 µL mg −1 . Therefore, this work paves a new avenue for boosting high‐performances Li–S batteries toward practical applications. Abstract : A holey Nb4 N5 ‐Nb2 O5 heterostructure is designed as a dual‐functional host for both the sulfur‐cathode and lithium‐anode for lithium‐sulfur full‐batteries. The polysulfide‐shutting is significantly alleviated as the accelerative polysulfides anchoring‐diffusion‐converting efficiency of the interface. A homogeneous lithium‐ion deposition is realized as the lithiophilic holey ion‐redistributor. The designed lithium‐sulfur full batteries present excellent electrochemical properties at high sulfur loading and lean electrolyte conditions.